Diagnosing and Identifying Standards Affecting on the Ready-Mix Concrete Production Plants Performance: An Analytical Study - Sara G.H. Hussein; Faiq M.S. Al-Zwainy (Tikrit Journal of Engineering Sciences, 2024)
Due to the rapid growth of the construction industry in Iraq, this study aims to identify and diagnose the reasons behind the poor performance of ready-mixed concrete production plants in Baghdad. This aim was achieved by analyzing the standards affecting the plants’ performance and identifying the cause of the deviation from their required performance using the root cause analysis technique through innovative tools and techniques, such as Pareto charts and the why technique. The study analyzed 35 reasons, divided into seven main groups: work breakdown structure, skills, shared values, systems, Administrative Styles, strategy, and staff. The results showed 23 out of 35 reasons with significant importance on the plants’ performance. The Pareto analysis revealed that nine causes out of 35 reasons were responsible for 80% of the poor plants’ performance. These included the lack of work breakdown structure in enhancing the functional performance of work teams and maximizing the utilization of their skills, as well as the insufficient number of work teams, two root causes of the work breakdown structure group. Another root cause from the skills group was the necessary skills lack among most work teams and the training programs and workshops absence for work teams. The study also found that the plant management's lack of focus on competition, excellence, and innovation was a root cause of the strategy group. In addition, the advanced techniques used for producing high-quality concrete mixes and the absence of a fair and accurate incentive and reward system were the root causes of the systems group. Furthermore, the management's failure to adopt control methods in all field and administrative work stages was a root cause of the management systems group, and the work teams' failure to adopt the knowledge-sharing approach was a root cause of the work teams' group. Using the "why" technique, it was found that the root cause was the absence of an objective, fair, and accurate incentive system in ready-mixed concrete production plants.